Sphingolipid metabolism-related genes B4GALNT1 and CERS4 as prognostic biomarkers in lung adenocarcinoma - Jieun Jeon; Junho Kang; Jae-Hyung Park; Jae-Ho Lee; Dong Eun Kim; Woo-Jae Park; Shin Kim (PLoS ONE, 2026)
Sphingolipid metabolism is an important component of various biological processes, particularly in cancer pathology. This metabolic pathway significantly influences the behavior of cancer cells by regulating growth, apoptosis, and survival. Although modulating sphingolipid metabolism has attracted attention as a novel therapeutic strategy, its complexity and specific mechanisms remain incompletely understood. In the current study, transcriptomic profiling was employed to compare the expression of sphingolipid metabolism-related genes between normal solid tissues and lung adenocarcinoma tissues. Additionally, Gene Ontology, Kyoto Encyclopedia of Genes and Genomes enrichment, and protein–protein interaction (PPI) analyses were performed to investigate the functional relevance of these genes. Twelve sphingolipid metabolism-related genes formed a highly interconnected core, suggesting their potential central role within the regulatory network. Four genes were found to be significantly correlated with overall survival. Notably, B4GALNT1 upregulation and CERS4 downregulation correlated with advanced tumor stage and metastasis. They also showed prognostic significance in Cox regression analyses, and these findings were consistently validated in an independent cohort. In vitro, within lung adenocarcinoma cell lines, B4GALNT1 knockdown and CERS4 overexpression suppressed cell proliferation, migration, and epithelial-to-mesenchymal transition, supporting their roles in lung adenocarcinoma progression. These findings highlight B4GALNT1 and CERS4 as potential prognostic biomarkers and therapeutic targets in lung adenocarcinoma, warranting further clinical investigation.